2010
DOI: 10.22230/jripe.2010v1n3a41
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Effects of Interprofessional Education on Undergraduate Students Behaviour: A Randomized Controlled Trial

Abstract: Background: One way to improve the quality of palliative care for elderly patients is to use an interprofessional team approach, which may be encouraged through interprofessional education (IPE). However, the effectiveness of IPE interventions has yet to be proven. We therefore designed a randomized controlled trial using a simulated practice setting to measure the effects of an IPE intervention on medical students’ clinical behaviour.Methods: Undergraduate nursing (N = 20) and medical (N = 20) students were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 22 publications
(23 reference statements)
1
30
0
Order By: Relevance
“…They also confirm that these levels may however initially be rather idealistic" (p562). The existence of poorer attitudes towards IPE was also noted by Just et al (2010) who reported that students with such attitudes, "tend to gain the least from IPE courses" (p194). A key element in the formation of these different attitudes towards IPE was seen as the professional socialisation processes (e.g.…”
Section: Learner Characteristicsmentioning
confidence: 81%
See 3 more Smart Citations
“…They also confirm that these levels may however initially be rather idealistic" (p562). The existence of poorer attitudes towards IPE was also noted by Just et al (2010) who reported that students with such attitudes, "tend to gain the least from IPE courses" (p194). A key element in the formation of these different attitudes towards IPE was seen as the professional socialisation processes (e.g.…”
Section: Learner Characteristicsmentioning
confidence: 81%
“…However, as noted above, most studies tended to include around 2 to 6 different professions with numbers usually ranging from 30-100 learners (e.g. Ammentorp et al 2007;Just et al 2010;Richardson et al 2010).…”
Section: Ipe Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…A precise manual of the developed UPCE curriculum and the respective teaching units can be found as Additional file 1 in the online section for this article. This publication assesses the effect on medical students completing the whole UPCE curriculum as an intervention, while a series of publications covers detailed analyses of the curriculum’s modules [17,18]. Qualitative analysis of encounters between dying patients and medical students during real patient contact in this curriculum has been covered by a master thesis at King’s College London, UK.…”
Section: Methodsmentioning
confidence: 99%